Evaluation of in situ and ex situ forage germplasm collections reveals the first occurrence and seed-transmission of alfalfa mosaic virus and southern bean mosaic virus in Urochloa species - Dawit, Woubit; Mulatu, Fikerte; Eshete, Yesuf; Negawo, Alemayehu T.; Kumar, Alok; Muchugi, Alice; Jones, Christopher S. (Taylor and Francis, 2024)
Grasses of the genus Urochloa (Urochloa species syn. Brachiaria species) are among the most important tropical forage grasses of African origin. The International Livestock Research Institute (ILRI) Forage Genebank maintains 671 Urochloa grass accessions, belonging to 28 species, of which 261 (39%) accessions are Urochloa brizantha (A.Rich.) R.D.Webster. The susceptibility of Urochloa grasses to disease and insect pests is a key challenge to the sustainable production of these grasses in Africa. In this study, using a dot blot assay and RT-PCR, we report for the first time the association of Alfalfa Mosaic Virus (AMV) and Southern Bean Mosaic Virus (SBMV) with 92% of the tested accessions conserved in situ and ex situ in the ILRI forage genebank. In addition, virus transmission from seed to plant and from legume to grass was confirmed through the bioassay test. The detection of these two viruses in Urochloa species presents a new challenge to germplasm conservation, distribution, and their sustainable production in the region, and demands immediate attention towards developing an effective method of cleaning viruses from the conserved germplasm. Furthermore, there is an urgent need to assess the economic importance of diseases in the grasses, and for the selection of germplasm that shows resistance to diseases.